PARTICIPATION NON-GOVERNMENTAL ORGANIZATIONS TO CONDUCT OF LEGAL MONITORING IN THE REPUBLIC OF KAZAKHSTAN - Yerbol Abaevich, Дюсенов; Olzhas Suyundikovich, Карахожаев (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article describes the issues of improving the legal monitoring, as well as important aspects of practice of the legal monitoring normative legal acts of state authorities the Republic of Kazakhstan. Given the content of the norms of the draft law "On Legal Acts" analysis and present proposals regarding the future development of the institute legal monitoring.